Response of soil Olsen-P to P budget under different long-term fertilization treatments in a fluvo-aquic soil - Wei-wei ZHANG; Xiao-ying ZHAN; Shu-xiang ZHANG; Khalid Hamdan Mohamed Ibrahima; Ming-gang XU (Journal of Integrative Agriculture, 2019)
The concentration of soil Olsen-P is rapidly increasing in many parts of China, where P budget (P input minus P output) is the main factor influencing soil Olsen-P. Understanding the relationship between soil Olsen-P and P budget is useful in estimating soil Olsen-P content and conducting P management strategies. To address this, a long-term experiment (1991–2011) was performed on a fluvo-aquic soil in Beijing, China, where seven fertilization treatments were used to study the response of soil Olsen-P to P budget. The results showed that the relationship between the decrease in soil Olsen-P and P deficit could be simulated by a simple linear model. In treatments without P fertilization (CK, N, and NK), soil Olsen-P decreased by 2.4, 1.9, and 1.4 mg kg–1 for every 100 kg ha–1 of P deficit, respectively. Under conditions of P addition, the relationship between the increase in soil Olsen-P and P surplus could be divided into two stages. When P surplus was lower than the range of 729–884 kg ha–1, soil Olsen-P fluctuated over the course of the experimental period with chemical fertilizers (NP and NPK), and increased by 5.0 and 2.0 mg kg–1, respectively, when treated with chemical fertilizers combined with manure (NPKM and 1.5NPKM) for every 100 kg ha–1 of P surplus. When P surplus was higher than the range of 729–884 kg ha–1, soil Olsen-P increased by 49.0 and 37.0 mg kg–1 in NPKM and 1.5NPKM treatments, respectively, for every 100 kg ha–1 P surplus. The relationship between the increase in soil Olsen-P and P surplus could be simulated by two-segment linear models. The cumulative P budget at the turning point was defined as the “storage threshold” of a fluvo-aquic soil in Beijing, and the storage thresholds under NPKM and 1.5NPKM were 729 and 884 kg ha–1 P for more adsorption sites. According to the critical soil P values (CPVs) and the relationship between soil Olsen-P and P budget, the quantity of P fertilizers for winter wheat could be increased and that of summer maize could be decreased based on the results of treatments in chemical fertilization. Additionally, when chemical fertilizers are combined with manures (NPKM and 1.5NPKM), it could take approximately 9–11 years for soil Olsen-P to decrease to the critical soil P values of crops grown in the absence of P fertilizer.